IDENTIFICATION OF FORMALDEHYDE CONTENT IN FISH SOLD IN SEVERAL TRADITIONAL MARKETS IN BANDUNG CITY - Lina Karlina; Junianto Junianto; Kiki Haetami; Iis Rostini (Jurnal Perikanan Unram, 2024)
Fish are one of the types of food that quickly spoil. The use of ice blocks as a preservation medium for fish is relatively expensive due to the large amount of ice required. Therefore, some traders use formalin as a fish preservative because it is considered more economical. The purpose of this research is to analyze the presence of formalin in fish sold in some traditional markets in Bandung City. The identification of formalin content was carried out qualitatively using the Nash reagent and quantitatively using the UV-Vis spectrophotometer. The analysis of four traditional markets and three types of fish found formalin in Kosambi Market and Gedebage Market. The identified fish species containing formalin were mackerel (Rastrelliger) and tuna mackerel (Euthynnus affinis). The highest formalin concentration was found in tuna mackerel (Euthynnus affinis), with a concentration of 1.79 mg/L.